Dynamic spinal orthoses self-reported effects in patients with back pain due to vertebral fragility fractures: A multi-center prospective cohort study - de Sire, Alessandro; Lippi, Lorenzo; Calafiore, Dario; Marotta, Nicola; Mezian, Kamal; Chiaramonte, Rita; Cisari, Carlo; Vecchio, Michele; Ammendolia, Antonio; Invernizzi, Marco (Journal of back and musculoskeletal rehabilitation, 2024)
BACKGROUND: Vertebral fragility fractures (VFFs) commonly result from low bone mass and microarchitecture deterioration of bone tissue. spinal orthoses are common non-pharmacological options for managing vertebral fracture pain. However, the effects of spinal orthoses on pain, physical functioning, and quality of life (QoL) are still debated. OBJECTIVE: This survey aimed to investigate the patients-reported outcomes of a dynamic spinal orthosis prescribed in the routine clinical practice of VFFs management. METHODS: This multi-center national-wide prospective cohort study assessed older patients (aged > 60 years) diagnosed with acute VFFs and prescribed with a dynamic spinal orthosis (Spinfast®). A survey questionnaire was realized and included sections on patient characterization, osteoporosis characterization, spinal orthosis, clinical outcomes, pain medications, and osteoporosis medications. The questionnaire was administered at baseline and after three months. A total of 68 patients completed the questionnaire at three months. Most patients had one or two VFFs and were treated with pain medications and osteoporosis medications. Compliance and tolerability of the spinal orthosis were assessed, and clinical outcomes such as pain intensity, physical functioning, and QoL were measured. RESULTS: The results showed no significant differences in outcomes between age subgroups. Italian physical medicine and rehabilitation physicians were commonly involved in the management of VFFs patients. Sixty-six patients completed the questionnaire. The results showed that pain intensity, physical functioning and QoL improved after three months of spinal orthosis wearing (p< 0.0001). CONCLUSION: The correct management of VFFs is mandatory to improve pain and reduce disability, and our findings suggested a positive role of dynamic spinal orthosis to improve the comprehensive management of VFFs patients. However, high-quality research trials are warranted to provide clear recommendations for the correct clinical management of VFF.
Keywords: fraktury páteře; Female; Pain Measurement; vertebral fractures; spine; hodnocení výsledků péče pacientem; Quality of Life; ženské pohlaví; protetické prostředky; kvalita života; Patient Reported Outcome Measures; lidé; Osteoporotic Fractures; Self Report; Back Pain; Osteoporosis; Aged, 80 and over; měření bolesti; rehabilitation; prospektivní studie; bolesti zad; Male; spinal orthoses; Orthotic Devices; Aged; Prospective Studies; lidé středního věku; osteoporotické fraktury; senioři nad 80 let; Spinal Fractures; senioři; mužské pohlaví; zpráva o sobě; Middle Aged; Humans